Financing long term care in Asia and the Pacific. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Financing is fundamental to any LTC system and is key to defining who will be covered, what they will be covered for, and what people must pay out of pocket. The brief looks at the current status of LTC financing systems in the region and key aspects such as revenue raising, pooling, passive and strategic purchasing, and coverage.
Keywords: Social rights -- Economic aspects; Finance -- Asia; Electronic book